Pharmacokinetics and Tolerability of a New Manidipine and Delapril Fixed Oral Combination in Young and Elderly Subjects - Stockis, Armel; Bruyn, Steven De; Gengler, Christophe; Goethals, Fabienne; Lens, Simone; Poli, Gianluigi; Acerbi, Daniela (Arzneimittelforschung, 2003)
The aim of the present study was to compare the pharmacokinetic and pharmacodynamic properties of a fixed combination tablet containing 10 mg of manidipine dihydrochloride (CAS 89226-75-5), a calcium channel antagonist, and 30 mg of delapril hydrochloride (CAS 83435-67-0), an angiotensin converting enzyme (ACE) inhibitor, during once daily repeated dosing in young and elderly subjects and to assess the bioequivalence of the fixed combination tablet and the single ingredient tablets taken simultaneously in young healthy subjects after a single dose administration.Eighteen young healthy male volunteers received a single oral dose of 10 mg manidipine and 30 mg delapril as two separate tablets or a fixed combination tablet, followed by a week of once daily dosing with the fixed combination. Eight male and eight female elderly volunteers also received a week of once daily dosing with the fixed combination. Blood samples were collected during 24 h on the first and last treatment day for plasma determination of manidipine, delapril and their main metabolites, using specific LC-MS/MS methods. Blood pressure and heart rate were also recorded during 24 h.Bioequivalence was strictly demonstrated between the extemporaneous and the fixed combination tablet after single dose administration. At steady-state in young subjects, manidipine AUC and Cmax were lower (-8 and −12 %) and t1⁄2 was longer (+ 45 %), while delapril and metabolites were little affected as compared to single dose. In elderly subjects, manidipine Cmax was 4 % lower than after single dose, AUC was 13 % higher, and t1⁄2 was increased 2.4-fold. For delapril and active metabolites, Cmax and AUC increased modestly. Blood pressure and heart rate versus time profiles after single dose and at steady-state were almost superimposable. In elderly compared to young subjects at steady-state, peak concentrations of manidipine and delapril changed by + 35 % and −15 % while AUCs increased by + 70 % and + 9.7 %.The fixed combination tablet of 10 mg manidipine and 30 mg delapril is bioequivalent to mono-ingredient tablets. At steady-state, the pharmacokinetic and pharmacodynamic profiles in young and elderly subjects undergo minor changes and indicate negligible accumulation. Drug exposure is higher in elderly subjects.
Keywords: CAS 83435-67-0; CAS 89226-75-5; Delapril, clinical pharmacokinetics, combination with manidipine, young and elderly subjects; Manidipine, clinical pharmacokinetics, combination with delapril, young and elderly subjects